Andalusia and Cordoba in Allama Muhammad Iqbal’s Perspective: An Analytical Study - Safeer, Muhammad; Lotfi, Farzaneh Azam; Bukhari, Sara Zahra (sourcecoder, 2024)
Since the Portuguese sailor Vasco de Gama had landed in Calicut in 1498 AD, the connection that had been established between East and Europe for years has been revived. The first connection based on historical sources was established in around 325-327 BC with the arrival of Alexander the Great in Punjab. The European invasion of the subcontinent lasted from 1500-1858, BC and just in the second century BC, Greek adventurers from Bactria to the Punjab and parts of Afghanistan established a state. This was the case until the end of the early century, and continued in the form of trade relations in various historical periods until the fall of the Roman Empire. Andalusia was the center of government and the flourishing of Islamic civilization for eight centuries, and the tolerance of Muslim rulers towards the defeated Spanish nation was the beginning of the message of Muslim peace in the West. Islam, under Goths rule, or the minority rule of non-religious and ecclesiastical aristocracy with the message of peaceful coexistence among religions and ethnicities paved way for flourishing of Islamic civilization in this land. The Cordoba Mosque is a symbol of development of the peaceful civilization of Muslims during that period. In Iqbal’s view, the trustee of the blood of the Muslims of the world is the result of this message. This study examines and analyzes the past glory of Muslims in Andalusia with the interpretation of Iqbal’s famous poem.